A POLIFONIA E A MODALIDADE COMPONDO A ESTRUTURA ARGUMENTATIVA DE DOIS TEXTOS JORNALÍSTICOS - Guerra, Vânia Maria Lescano; Maher, Sônia Maria Corsa; Nogueira, Teresinha de Fátima; Nogueira, Maria Cristina de Siqueira (Intercâmbio, 2010)
This article aims at demonstrating how the concepts of poliphony and modality interrelate to form different argumentative structures. Although we have compared two differently organized newspaper texts, the effects of argumentation were similar.